2021
DOI: 10.3390/atmos12101318
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Performance of Different Interpolation Methods in Replicating Rainfall Magnitudes under Different Climatic Conditions in Chongqing Province (China)

Abstract: Precipitation is considered a crucial component in the hydrological cycle and changes in its spatial pattern directly influence the water resources. We compare different interpolation techniques in predicting the spatial distribution pattern of precipitation in Chongqing. Six interpolation methods, i.e., Inverse Distance Weighting (IDW), Radial Basis Function (RBF), Diffusion Interpolation with Barrier (DIB), Kernel Interpolation with Barrier (KIB), Ordinary Kriging (OK) and Empirical Bayesian Kriging (EBK), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 53 publications
(127 reference statements)
0
17
0
Order By: Relevance
“…Whenever there is a spatially correlated distance or directional bias in the data, kriging is the best method to use [ 55 ]. For examining spatial variability in the data, a variogram model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Whenever there is a spatially correlated distance or directional bias in the data, kriging is the best method to use [ 55 ]. For examining spatial variability in the data, a variogram model was used.…”
Section: Resultsmentioning
confidence: 99%
“…EBK, a combination of the kriging interpolation technique and Bayes' theory, is a simple and reliable method for automatic data interpolation of the variables [15,25,34]. As a result, EBK users do not have to manually interfere with the variables to obtain more accurate results [35].…”
Section: Empirical Bayesian Kriging (Ebk)mentioning
confidence: 99%
“…Antal et al [24] compared local polynomial interpolation (LPI), radial basis function (RBF), global polynomial interpolation (GPI), empirical Bayesian kriging regression (EBKR), universal cokriging (UCoK), IDW, and OCoK methods using annual precipitation data in Portugal, and they found that the EBKR method provided the most outstanding performance. Yang and Xing [25] compared kernel interpolation with barrier (KIB), diffusion interpolation with barrier (DIB), IDW, RBF, OK, and EBK methods using precipitation data from different time series in Chongqing (China), and they found that the KIB method provided the highest accuracy. Caloiero et al [26] compared the IDW, OK, KED, and OCoK methods using monthly precipitation data in New Zealand and found OCoK to be the optimal method.…”
Section: Introductionmentioning
confidence: 99%
“…Several interpolation techniques are available to produce gridded maps from scattered in situ measurements of climate variables (Chen & Guo, 2017; Hofstra et al, 2008; Yang & Xing, 2021) and most of them are implemented in software packages for the R language (R Core Team, 2021). For example, gstat (Pebesma, 2004) is a well‐known and user‐friendly R package which implements both deterministic (inverse distance weighting [IDW]) and geostatistical (traditional kriging and its variants) methods.…”
Section: Introductionmentioning
confidence: 99%